On a Fair Fare Rating an a Bus Line - Stanislav Paluch (Communications - Scientific letters of the University of Zilina, 2013)
Suppose we are given along bus line with asingle tariff. Some passengers travel along long distances while another ones along short trips. Such asingle tariff is advantageous for the first mentioned passengers. However, asingle tariff is inconvenient for short trip passengers. Babel, Keller, Hamacher and Schobel tried to solve this problem by dividing serviced area into zones in [1], [2] and [3]. Kohani presented similar attitude in [4]. Another way how to improve fairness is to introduce a double tariff – fare x for passengers traveling at most along k laps and fare y for passengers traveling along more than k laps. This paper shows how to determine optimal values k, x and y.